Methods of protection and the state of preservation of the walls topping of Gothic brick castles - Trochonowicz, Maciej; Drobek, Katarzyna (Budownictwo i Architektura / Civil and Architectural Engineering, 2022)
This article is an analysis of methods of securing historic walls in objects in the form of so-called permanent ruins. The research group consists of the brick Gothic castles of Mazovia in Ciechanów, Czersk, Liw and Sochaczew. Based on the analysis of documentation and our research, the effectiveness of the solutions applied in 4 different technological variants was evaluated. The state of preservation of the introduced solutions after several years of work was also assessed. The entire study was summarised in a table and conclusions were drawn.